ANALISIS PERBANDINGAN KINERJA KEUANGAN BJB SYARIAH DAN BRI SYARIAH TAHUN TAHUN 2016-2020 - Balqis, Syafira Laras; Thantawi, Tubagus Rifqy; Rizal, Muhammad (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This study aims to determine the financial performance of PT. Bank BJB Syariah and PT. Bank BRI Syariah is also conducting comparisons in 2016-2020. The subject of this research is PT. Bank BJB Syariah and PT. Bank BRI Syariah. In this study using library research methods (research library and documentation study). The results of this study are that there is no significant difference between the ROE of BJB Syariah and BRI Syariah, namely the value of sig 0.916 > 0.000. There is no difference between the CAR of BJB Syariah and BRI Sharia significantly, because the sig obtained is 0.262 > 0.05. There is a significant difference between the ROA of BJB Syariah and BRI Syariah, because the sig obtained is 0.000 <0.05. It can be concluded that it is unlikely that the BRI Syariah bank will experience However, it is different from ROA at bank BJB Syariah which has fluctuated from 2018 to 2020.